2003
DOI: 10.3349/ymj.2003.44.3.473
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Polyethylene Wear in Total Hip Arthroplasty: Accuracy Versus Ease of Use

Abstract: The aim of this study was to compare the accuracy of four different methods for measuring wear using an apparatus that simulates known amounts of three dimensional wear. Wear was measured using the manual methods reported by Charnley, Livermore, Dorr and Wan and the computerized method reported by Devane. Only the method reported by Devane measured the three-dimensional (superior and anterior) wear with a reasonable accuracy, with a mean measurement error of 0.21 mm. With superior wear alone, Charnley's method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 0 publications
0
20
0
1
Order By: Relevance
“…The techniques of Livermore, Charnley, and others were described and validated in the era of the monoblock, all-polyethylene, and cemented acetabular component, and different markers were selected [17-25]. The Dorr technique uses the opening face of the acetabular component as the reference and bases its measurements on a single radiograph [16].…”
Section: Discussionmentioning
confidence: 99%
“…The techniques of Livermore, Charnley, and others were described and validated in the era of the monoblock, all-polyethylene, and cemented acetabular component, and different markers were selected [17-25]. The Dorr technique uses the opening face of the acetabular component as the reference and bases its measurements on a single radiograph [16].…”
Section: Discussionmentioning
confidence: 99%
“…Devane et al 5 tested the first semiautomatic PolyWare version and determined a 3D accuracy of ±0.15 mm for 3D linear wear, whereas Kang et al 10 estimated the 2D and 3D measurement error of the software in a phantom setting to 0.15 and 0.21 mm, respectively. Ebramzadeh et al 11 concluded that the 3D measurement error (mean difference from the micrometer true value) with PolyWare was 0.10 mm (mean and median) with the use of laboratory radiographs of a phantom.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the mean error of the Dorr technique was much less in our study than in the above-mentioned studies (Table 1). Interestingly, a modification of the Dorr method taking into account the wear direction has been published recently 25 . Unfortunately, …”
Section: Discussionmentioning
confidence: 99%